2019
DOI: 10.1111/bju.14900
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes of salvage robot‐assisted laparoscopic prostatectomy for post‐primary radiation vs focal therapy

Abstract: Objectives To compare salvage robot‐assisted laparoscopic prostatectomy (RALP) outcomes in patients who underwent radiation and those who underwent focal ablation as primary therapies. Patients and Methods We evaluated 126 patients who underwent salvage RALPbetween 2008 and 2018. Of these, 94 (74.6%) received radiation and 32 focal ablation (25.4%) as primary therapy. These groups were compared with regard to clinical, oncological and functional outcomes. Kaplan–Meier curves and regression models were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…In the absence of RCTs, all 23 studies that reported oncologic outcomes and were included in the analyses were of retrospective design (19 single center [12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and four multi center [5,[35][36][37]). The studies were published between 1988 and 2020.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…In the absence of RCTs, all 23 studies that reported oncologic outcomes and were included in the analyses were of retrospective design (19 single center [12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and four multi center [5,[35][36][37]). The studies were published between 1988 and 2020.…”
Section: Epidemiologymentioning
confidence: 99%
“…The overall median time to SRP was 51 months (IQR 41-69) and overall median total serum PSA at SRP was 6.04 ng/mL (IQR 4.5-9.4). Information on the surgical technique was provided in 12 studies [5,12,[18][19][20][21][22][23][24]31,32,35], compromising 1277 patients. SRP was performed in open approach in 79.9% of the patients, robotic in 19.0%, and laparoscopic in 1.1%.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations